Customer relationship management in the financial industry : organizational processes and technology innovation - Rajola, Federico (Management for Professionals, 2013)
An integrated view of IT and business processes through extended IT governance allows financial institutions to innovate operations which improve business and organizational performance. However, financial institutions still face challenges with CRM systems in delivering expected results due to lack of complete business integration.  Increased exchange of knowledge between customers and the amount of such data available is steadily becoming a challenge for companies, especially in extending internal systems to global information systems with the purpose to collect and update data on a global scale. In this book, Prof. Rajola analyses different aspects of CRM systems taking both an organizational and a technological perspective.  He adopts a theoretical framework to unpack issues associated with the need for companies to integrate operations and business processes. The emphasis is then drawn to development of effective CRM (and CRM 2.0) initiatives by making use of illustrative case studies of successful CRM systems implementation in the financial industry. The framework adopted in this book can be used by both scholars and managers to evaluate the interdependencies between operations, business processes, and CRM systems.   .